Tauf Protocol vor die Reformirte Gemeinde in Lohill, Northampton County (Filmed by the Genealogical Society of Utah, 1981)
Description Not Provided

Lowhill Church, Lowhill Twp., Lehigh County, Pa (Pennsylvania genealogical findings in the Allemangel area of Berks and Lehigh counties and adjoining areas, source no. 9,, 1984)
Description Not Provided
Includes a history, tax lists 1762, 1781, first settlers, early church members, baptisms, ca. 1772-ca. 1980 with some marriages also.

Lowhill Reformed Church, New Tripoli, R.D., Lehigh Co., Pa., index to baptismal record 1769-1798 ; St. Paul's Church, Trexlertown, Pa., index to church records 1784-1882 (Filmed by the Genealogical Society of Utah, 1981)
Description Not Provided

Tauf protocol vor die reformirte Gemeinde in Lohill, Northampton County, begun by Johann Heinrich Helffrich ... 1772 Reformed Church, Weissenburg Township, Lehigh Co., Pa (Filmed by the Genealogical Society of Utah, 1973)
Description Not Provided
Contains Lowhill Reformed Church baptisms 1769-1870, 1881; account book and bylaws (union). Includes unpaged "Kirchen buch vor die Gemeinde Glieder die zu der Weisseburger Kirche ..." church officials, baptisms 1737-1862 (Lutheran and Reformed intermixed after 1793); Lutheran confirmations 1760-1765, marriages 1758-1765, deaths 1752-1765 (some without dates).

Church records: 1774-1817 (Filmed by the Genealogical Society of Utah, 1947)
Church was organized in 1769 by dissatisfied members of the Weisenberg Church. Lowhill is located in Lowhill Township near New Tripoli.

Pastor's record, 1816-1861: Reformed churches in Lehigh Co. at Heidelberg, Lyntown or Ebenezer, Lowhill, Weisenberg and Ziegels; in Berks Co. Longswamp (Filmed by the Genealogical Society of Utah, 1993)
Rev. Helffrich served Ziegel's Charge 1816-1852. Entries to 1862 are by another, probably William Helffrich.